2023
DOI: 10.3390/ijms241311201
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs in Neurological Manifestation in Patients Co-Infected with SARS-CoV-2 and Herpesvírus 6 (HHV-6)

Abstract: Human herpesviruses (HHVs) can establish latency and be reactivated, also are neurotropic viruses that can trigger neurological disorders. HHV-6 is a herpesvirus that is associated with neurological disorders. Studies have reported the detection of HHV-6 in patients with COVID-19 and neurological manifestations. However, specific diagnoses of the neurological disorders caused by these viruses tend to be invasive or difficult to interpret. This study aimed to establish a relationship between miRNA and neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Furthermore, the down-regulation of miR-let-7b-5p in EBV-infected B cells compared to that in uninfected B cells provides evidence that EBV infection down-regulates miR-let-7b-5p, including MS-risk miRNAs, which may contribute to MS pathogenesis via direct or indirect interaction with risk genes [91]. In a study conducted by our group, we found a significant increase in miR-let-7b-5p expression in a group of patients with HHV-6 infection and neurological manifestations, which encouraged studies investigating the role of this miRNA in neurological complications caused by HHV-6 [16].…”
Section: Mir-let-7a and Mir-let-7bmentioning
confidence: 54%
See 1 more Smart Citation
“…Furthermore, the down-regulation of miR-let-7b-5p in EBV-infected B cells compared to that in uninfected B cells provides evidence that EBV infection down-regulates miR-let-7b-5p, including MS-risk miRNAs, which may contribute to MS pathogenesis via direct or indirect interaction with risk genes [91]. In a study conducted by our group, we found a significant increase in miR-let-7b-5p expression in a group of patients with HHV-6 infection and neurological manifestations, which encouraged studies investigating the role of this miRNA in neurological complications caused by HHV-6 [16].…”
Section: Mir-let-7a and Mir-let-7bmentioning
confidence: 54%
“…Therefore, investigations into biomarkers for neurological diseases are growing [13][14][15]. Recently, our group identified differentially expressed mi-croRNAs (miRNAs) in a cohort of patients with COVID-19, who had HHV-6 detection and neurological symptoms [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, diagnosing these neurological disorders caused by the viruses can be invasive and challenging. The study by Carneiro et al aimed to establish a connection between microRNAs (miRNA) and neurological symptoms in patients co-infected with COVID-19 and HHV-6, as well as to explore the potential of miRNAs as biomarkers [ 40 ]. The study analyzed serum samples from three groups of COVID-19 patients.…”
Section: An Overview Of Published Articlesmentioning
confidence: 99%